Laser direct metal deposition process of thin-walled parts using variable spot by inside-beam powder feeding. Issue 1 (2nd January 2018) - Wang, Lifang; Zhu, Gangxian; Shi, Tuo; Wu, Jizhuo; Lu, Bin; Fu, Geyan; Ye, Yunxia
Abstract : Purpose: The purpose of this paper is to improve the forming efficiency and quality of unequal-width parts fabricated by laser direct metal deposition technology, some experiments were designed. Design/methodology/approach: A new method by varying laser spot was adopted to fabricate unequal-width single track using one scanning rather than multi-track overlapping in the way of the inside-beam powder feeding, and the thin-walled parts were fabricated layer by layer. The theoretical model among layer thickness of z -axis, height of single track and the section curve order of single track was established. Findings: The top surface unevenness of the thin-walled parts could be compensated automatically within the laser defocusing ranges from −2.5 to −5 mm and from 0.5 to 2.5 mm. The growth rate with the large width/height ratio was more than the small ratio, while the set height of the single track was uniform. The problem of non-uniform growth rate could be solved based on a stepped single-track method. The thin-walled parts with the smooth top surface was fabricated layer by layer which had a continuously variable width from 1 to 3 mm by splicing the laser defocusing range. Practical implications: The shapes of the to-be-fabricated parts affect variable laser spot process in practical applications. For example, it will be difficult to apply variable laser spot process on the parts with the hole features. Originality/value: This paper provided a guidance for forming unequal-width parts by laser direct metal deposition based on the inside-beam powder feeding.